Raman spectrum identification based on the correlation score using the weighted segmental hit quality index. Issue 2 (9th January 2017) - Park, Jun-Kyu; Park, Aaron; Yang, Si Kyung; Baek, Sung-June; Hwang, Joonki; Choo, Jaebum
Abstract : In this paper, we consider a novel method for identification of Raman spectra recorded on different instruments with different wavelengths. Abstract : In this paper, we consider a novel method for identification of Raman spectra recorded on different instruments with different wavelengths. Since the conventional hit quality index (HQI) is vulnerable to intensity variation, it needs intensity calibration or standardization for each spectrometer, which causes additional time consuming work. To simplify this process and enhance the identification performance, we propose a new scoring method which is defined as the weighted sum of the HQIs from segmented spectra by windowing. To show the effectiveness of the proposed method, the experiments were carried out with 10 kinds of chemicals with their spectra recorded on 3 different instruments with different laser wavelengths. According to the identification results with 14 033 chemicals, the proposed method identified all test chemicals without error, which indicates that the proposed method could be used as a promising alternative to the existing methods.